MAIsCap-MARKETING ARCHITECTURAL ISOLATING CAPABILITY AS ANTECEDENTS FOR SUCCESS OFNEW PRODUCT DEVELOPMENT - Augusty Tae Ferdinand; Kardison Lumban Batu (Universitas Hayam Wuruk Perbanas, 2013)
This study is a basic research for fulfilling research gap in New Product Development studies. Even though a new productdevelopment program is a high cost program, the level of success in entering the market is stilllow. This issue rises a question what should beconsidered in arranging ways to increase the success rate of new product development. This study proposes a concept of MAIsCAp-Marketing Architectural Isolating Capability, together with the concept of Competitive Experience Portfolio and Marketing Resource Flexibility postulated as hold a key role in enhancing the new product development Orgware quality as a prerequisite for enhancing new product marketing performance. Seven hypotheses were developed and tested using the data which were collected from 355 respondents serving as Product Development Manager and Marketing Manager in Indonesia. Data was analyzed using SEM AMOS 21 Statistical Software which supported 6 hypotheses. This study indicated that MAIsCap holds a strategic anchor position for strengthening NPD Orgware Quality in enhancing new product marketing performance.